Adhesion Prevention in Operative Laparoscopy - Wachyu Hadisaputra (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To know the modalities used for prevention of adhesion formation in operative laparoscopy. Method: Literature study. Results: Methods of prevention of adhesion in laparoscopy include: modification of surgical technique, anti-inflammatory agents, peritoneal instillates and barrier adjuvants. Modification of surgical techniques such as adherence to basic principles of microsurgery, the use of electrothermal bipolar vessel sealer, liberal irigation of the abdominal cavity and instillation of a large amount of Ringer’s lactate at the completion of the procedure. This technique alone, eventhough seems effective, is insufficient. The anti-inflammatory agents used are the NSAIDs, corticosteroids, antihistamines, progestogens, GnRH agonists and calcium channel blocker. But none of them demonstrated to be significantly effective. Barrier adjuvants consist of: oxidized regenerated cellulose (ORC) and expanded polytetrafluoroethylene (ePTFE) and peritoneal instillates are the crystalloids, icodextrin, hyaluronic acid (HA), solution of HA, viscoelastic gel, hydrogel, and fibrin sealent. There is insufficient evidence data regarding the methods above for the prevention of adhesiogenesis in laparoscopy. But one study evaluating the use of viscoelastic gel did significantly reduce adnexal adhesion in laparoscopy. Conclusion: Laparoscopy does not trully eliminate the adhesiogenesis problem. No single therapy is effective for prevention of adhesion formation. The multimodal methods shall be used to increase the successful rate in adhesion prevention. [Indones J Obstet Gynecol 2010; 34-4: 204-7] Keywords: laparoscopy, adhesion, microsurgery, anti-inflammatory, peritoneal instillates, barrier adjuvants